Penerapan Model Pembelajaran Inovatif Dalam Bahasa Arab Bagi Alumni Departemen Sastra Arab Universitas Negeri Malang: Model Inovatif Dalam Pembelajaran Bahasa Arab - Nurhidayati; Fauzan, Moh; Ahsanuddin, Mohammad; Wahib Dariyadi, Moch.; Fery Fauzi, Moh (Tifani : Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This service was carried out as a form of concern for the Department of Arabic Literature, Faculty of Letters, State University of Malang (JSA FS UM) towards graduates. In this training, the gate will be equipped with knowledge and application of several innovative learning models in Arabic language learning. The learning models in question are Problem-Based Learning (PBL), Project Based Learning (PjBL), and Discovery Learning (DL) models. These learning models will be applied in Arabic language learning. The details of the application of the three models are contained in 7 materials presented by the speakers. After delivering the material, the activity organizers assisted the participants in practicing. This assistance is carried out online and offline. Service is provided in learning for five weeks. Every week, participants are given a tutorial on designing the application of Arabic language learning models, and participants create articles related to the application of innovative learning models in Arabic. Fifty participants attended this activity. As evaluation material, the activity implementer distributed a questionnaire via Google Forms after the action was carried out. The results of the questionnaire are as follows: The facilities provided by the facilitator. 90.9% of participants said it was perfect, and 9.1% said it was good. The questionnaire results are related to the resource person's mastery of the material. 75% of participants stated that the resource person mastered the material, and 22.7% noted that the resource person got the material. The questionnaire results related to the resource person's clarity in delivering the material. 72.7% of participants stated that the resource person clearly explained the material, and 25% said the speaker's explanation was clear. The questionnaire results are related to the usefulness of the material in learning innovation. 86.4% of participants stated that the activity resource was very useful in learning innovation, and 13.6% noted that the activity helped them learn creation.